The Influence of Accounting Profit, Audit Fee, Audit Opinion, Company Operational Complexity on Audit Delay - Dewi Agustin; Suryani Yuli Astuti; Ira Megasyara; Devi Febrianti (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2026)
This study aims to analyze the influence of accounting profit, audit fees, audit opinions, and company operational complexity on audit delay in companies in the energy sector’s oil, gas, and coal subsectors listed on the Indonesia Stock Exchange during the 2021-2023 period. The research population consists of 82 companies. This study employs a quantitative causal approach using secondary data in the form of audited annual reports. Using purposive sampling, 50 companies met the sampling criteria, resulting in 150 observations. Hypothesis testing was conducted using logistic regression with IBM SPSS version 25. Research's results indicate that audit fees influence audit delays, while the company operational complexity significantly affects audit delays, however, accounting profit and audit opinions do not influence audit delays. The novelty of this study lies in the use of logistic regression with audit delay measured via a dummy variable, its focus on the oil, gas, and coal subsector period 2021-2023, and the integration of four variables into a single analysis. This research provides an empirical contribution to the development of audit delay literature and serves as a basis for consideration by company management, auditors, regulators, and investors in enhancing the efficiency and promptness of financial reporting audits. Abstrak - Penelitian ini bertujuan untuk menganalisis pengaruh laba akuntansi, audit fee, opini audit, dan kompleksitas operasi perusahaan terhadap audit delay pada perusahaan sektor energi subsektor oil, gas & coal yang terdaftar di Bursa Efek Indonesia periode 2021-2023. Populasi penelitian terdiri dari 82 perusahaan. Penelitian ini menggunakan pendekatan kuantitatif kausalitas dengan data sekunder berupa annual report yang telah diaudit. Dengan menggunakan teknik purposive sampling, sebanyak 50 perusahaan memenuhi kriteria sampel sehingga diperoleh 150 observasi. Pengujian hipotesis dilakukan menggunakan regresi logistik dengan menggunakan IBM SPSS versi 25. Hasil riset memperlihatkan bahwa audit fee berpengaruh terhadap audit delay, kompleksitas operasi perusahaan berpengaruh signifikan terhadap audit delay, sedangkan laba akuntansi dan opini audit tidak berpengaruh terhadap audit delay. Keterbaharuan penelitian ini terletak pada penggunaan regresi logistik dengan pengukuran audit delay menggunakan variabel dummy, fokus pada subsektor oil, gas & coal periode 2021-2023, serta mengintegrasikan empat variabel ke dalam satu pengujian. Riset ini memberikan kontribusi empiris bagi pengembangan literatur audit delay serta menjadi bahan pertimbangan bagi manajemen perusahaan, auditor, regulator dan investor dalam meningkatkan efisiensi dan ketepatan waktu pelaporan keuangan auditan.